Knowledge graph construction and dissemination analysis in folk culture space: a case study of Wuzhen Xiangshi - Zhang, Haijing; Xu, Jun; Zhang, Hao (Frontiers in Communication, 2026)
Purpose/significanceIn the era of network self-media, online communication plays a crucial role in promoting the development of folk tourism. The computational communication method is utilized to analyze and visualize the communication content of the spatial elements of folk culture space, which is helpful for the development of folk culture space and the dissemination of national culture.Method/processInitially, the technical methodology of the knowledge graph was introduced, and an ontology model of cultural space was developed from the perspective of folk tourism. Utilizing the CIDOC-CRM model, the entity classes, attributes, and relationships were modeled, the core elements of cultural space were extracted from the description of cultural space by natural language analysis, and a knowledge graph was constructed. Building on this foundation, the network communication content of each element was collected, cleaned, and aligned. Utilizing computational communication methods, a multidimensional analysis of the network communication content for each element was conducted, and its communication, friendliness, influence, and interaction were studied. The public’s communication preferences and the emotional tendency of the spatial elements of folk culture space were explored. Finally, the communication content is embedded into the graph to form a communication-oriented knowledge graph of the spatial elements of the folk culture space oriented toward communication, and the systematic and structured representation of the knowledge graph is realized.Result/conclusionTaking Wuzhen Xiangshi, a cultural space in the ancient water town located in the south of the Yangtze River, as a case study, this research constructs a knowledge map of the elements of Wuzhen Xiangshi oriented to communication and analyzes its communication characteristics to provide reference and help for the organization and dissemination of folk culture space.